Fipronil, fenpropathrin and lambda cyhalothrin application alters defense related biomolecules composition favoring the resurgence of chilli thrips (Scirtothrips dorsalis) - T. Hemadri; M. Bheemanna; D. Srinivasa Reddy; Arunkumar Hosamani; R. Harischandra Naik; Saroja N. Rao; Nagaraj M. Naik; L. Rajesh Chowdary; Srikanth Barkeer; Keerthi Mc; B.L. Manisha; Wael Elmenofy; et al. (Journal of Asia-Pacific Entomology, 2026)

Electrochemical detection of gallic acid using carboxylic acid-functionalized carbon black integrated with an iron disulfide nanocomposite for sensitive and selective analysis of natural food samples - Nithishkumar Marimuthu; Arunkumar Selvam; Huda F. Khalil; Mohammed M. Algaradah; Vairamuthu Raj; Chih-Yu Kuo; Mani Govindasamy (Food Chemistry, 2026)

Study on the Mechanical, Microstructural, and Environmental Assessment of Concrete Containing High Volume Fly Ash and Waste Tyre Steel Fibers - Sankar B; Rameshkumar D; Gautham Kishore Reddy; Arunkumar K; Vishnuprasad V Prabhakar; Anamika S M (Circular Economy and Sustainability, 2026)

Resistance-guided isolation and identification of antibiotic-resistant bacteria from bull semen: exploring alternatives to antibiotics in semen extenders - Dileep Kumar Yadav; H. M. Rashmi; Manisha Sethi; Ramasamy Arunkumar; Pawan Singh; Nishant Kumar (Tropical Animal Health and Production, 2026)

Integrated evaluation of direct-expansion solar-assisted heat pump systems with climate-compatible refrigerants using life cycle impact and cost metrics - Arunkumar Munimathan; K. Senthil Kumar; M. Kannan; Ratchagaraja Dhairiyasamy; Mamdooh Alwetaishi; Ali Keçebaş (Energy and Buildings, 2026)

A synergistic approach to water purification: SERS-assisted detection and nanofiltration of contaminants in natural rubber wastewater using graphene oxide noble-metal nanocomposites - I.Anushma Jeffrin; Arunkumar Selvam; R. Parimaladevi; Vasant Sathe; Mohamed A. Habila; Chih-Yu Kuo; M. Umadevi (Journal of Environmental Chemical Engineering, 2026)

Eco-friendly synthesis of CuO nanoparticles using charcoal extract:Sustainable approach and mechanistic study of RhB dye degradation - M. Jothibas; B. Arunkumar; Abishake David Padmarajan; Kartheka Anandan; R. Sweet Stanly; Agalya Mathivanan; R. Piriyadharsini (Nanotechnology for Environmental Engineering, 2026)

Computational screening of lichen bioactive compounds as a potential antiviral agent against SARS-CoV-2 main proteases - S. Jeya Preethi; A. Yamuna; M. Arunkumar; E. Murugesh; P. Ponmurugan; P. Shanmughavel (In Silico Pharmacology, 2026)

Hybrid PCM-embedded concrete for thermal energy storage and energy-efficient smart buildings - S. Deepa Shri; Ali B. M. Ali; Arunkumar Munimathan; Ratchagaraja Dhairiyasamy; M. Kannan; Mukhtar Hamid Abed; Mohammad Amir Khan; Aseel Smerat (Innovative Infrastructure Solutions, 2026)

Evaluation of stable reference genes for RT-qPCR analysis in Antheraea assamensis (Lepidoptera: Saturniidae) during pathogenic infections - Indumathi Kamatchi Balakrishnan; Himanshu Dubey; Pawan Shukla; Rajal Debnath; C. Vanitha; Gangavarapu Subrahmanyam; Manthira moorthy; Kallare P. Arunkumar; Vikram Kumar; Abhishek Singh; K. M. Ponnuvel (Molecular Biology Reports, 2025)

Testicular thermoregulation and blood perfusion score as markers of sperm quality in summer-stressed breeding bulls - D. Lakhanpal; T. K. Mohanty; M. Bhakat; R. Arunkumar; D. Nain; R. Baithalu (Tropical Animal Health and Production, 2025)

Eco-conscious synthesis of chitosan-reduced magnetic Iron oxide nanocomposite from crab Shell waste for photocatalytic degradation of textile dyes: Ecotoxicity insights - Santhosh Abhirami; Govindhan Thiruppathi; Mohammad Shamsul Ola; M. Arunkumar; Palanisamy Sundararaj; Pawlin Vasanthi Joseph (Journal of Water Process Engineering, 2025)

Green synthesis of silver nanoparticles using Ocimum sanctum for efficient Congo red dye removal: a response surface methodology approach - S. Murugeshwari; B. Senthil Rathi; N. Kalaiarasi; R. M. Saravana Kumar; I. Arunkumar; M. Vasanth; P. Senthil Kumar; Gayathri Rangasamy (Environmental Monitoring and Assessment, 2025)

Microwave-assisted in-Situ Synthesis of ZnS/g-C3N4 Heterojunction Composite for Efficient Photocatalytic Degradation of Malachite Green Dye - Gomathi Ramalingam; Priya Arunkumar; Mashael Daghash Alqahtani; Ahmed M. Elgarahy (Water, Air, & Soil Pollution, 2025)

Biological and genomic characterization of a cypovirus isolated from golden muga silkworm, Antheraea assamensis Helfer (Lepidoptera: Saturniidae) - Iyyangar Deepika; Abhishek Singh; Indira Kumar; Gowtham K; Roja Gnanasekaran; Himanshu Dubey; Rajal Debnath; Pawan Shukla; Kangayam M. Ponnuvel; Vikram Kumar; K.P. Arunkumar; Hanamant Gadad; et al. (Journal of Invertebrate Pathology, 2025)

Stilt floor optimization based on stiffness and column contribution - R. Kavitha; G. Keertiga; D. Suryakrishnan; N. Santhakrishnan; M. Arunkumar (Innovative Infrastructure Solutions, 2025)

Microalgal Neutral Lipid Accumulation: Cellular Mechanism and Ways to Improve Biodiesel Production - M. Sreelakshmi; K. Arunkumar (BioEnergy Research, 2025)

Cleaner production of performance-enhanced hybrid composites using agro-industrial wastes: A sustainable waste management strategy - B. Prabhu; M. Prakash; N. Ramasamy; Viswanathan Kanagasabai; T. Mohanraj; D. Vijay; T. Arunkumar (Journal of Environmental Management, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Novel biosynthesized zinc selenite photocatalysts for enhanced degradation of oxytetracycline and Rhodamine B dye with antibacterial activity - A. Anitha; P. Ponmurugan; D. Arunkumar; C. S. Sumathi; M. Sathishkumar; T. Purushothaman (BioMetals, 2025)

Exploring potential biological applications of green derived silver nanoparticles using Codiaeum variegatum leaf extract - Arunkumar Lagashetty; M Anusha; Rachana; M Channabasavaraja; Shivakumar; V Veena; R․K Preeti; Sangappa K. Ganiger (Next Research, 2025)

Bioactive food polysaccharides: A review on sources, classification, and its potential health benefits in humans - Dharanie S; Meghana CH; Lavanya M; Baskaran N; Arunkumar Elumalai; Vignesh S (Food and Humanity, 2024)

Phenological Stages of Pink Pulp Dragon Fruit (Hylocereus costaricensis Web.): Codification and Description According to the Extended BBCH Scale Under Field Conditions - M. Kavino; G. Arunkumar (Applied Fruit Science, 2024)

Prospectus of hydrogen enrichment in internal combustion engines: Methodological insights on its production, injection, properties, performance and emissions - J. Jayaprabakar; T. Arunkumar; Gayathri Rangasamy; J. Parthipan; M. Anish; Gaddey Varshini; B. Kiran Kumar (Fuel, 2024)

Combating Alcohol Adduct Impurity in Immunosuppressant Drug Product Manufacturing: A Scientific Investigation for Enhanced Process Control - Vasanthakumar Sekar; Devarajan Vedhachalam; ArunKumar VB; Sivananthan Sivaraman; Venkatakrishnan Janakarajan; Sai Sethuraman; Sandeep G. Shiroor; Jean-Marie M. Geoffroy (Pharmaceutical Research, 2024)

Formation of NixCo1-xSe2 nanobelt solid solutions as competent electrode material for hybrid supercapattery - K.P. Annnamalai; N. Bhuvaneswari; M. Arunkumar; M. Sathish (Chemical Engineering Journal, 2024)

(Re)-thinking the red seaweed biomass for biofuel production to meet sustainable development goals toward circular bioeconomy - M. P. Sudhakar; K. Arunkumar; G. Dharani; Thangavel Mathimani (Energy, Ecology and Environment, 2024)

In Vitro Plant Growth Promoting Effect of Fucoidan Fractions of Turbinaria decurrens for Seed Germination, Organogenesis, and Adventitious Root Formation in Finger Millet and Eggplant - Arya Kaniyassery; Sachin Ashok Thorat; Nagarajan Shanthi; Shashikala Tantry; M. P. Sudhakar; Kulanthaiyesu Arunkumar; Annamalai Muthusamy (Journal of Plant Growth Regulation, 2024)
Bioactive ingredients derived from brown algae have been extensively used in the food, medicine, and cosmetic industries. In this study, fucoidans of low and high molecular fractions (LMF and HMF) extracted and isolated from brown alga Turbinaria decurrens were analyzed for their efficacy on seed germination, seedling growth, callus induction, direct organogenesis, and adventitious root formation in eggplant and finger millet. The yield and sugar content of LMF were higher than HMF. FTIR confirmed that the isolated fractions containing fucoidan has more sulfate groups in HMF than in LMF. The results showed an enhanced seed germination and seedling growth in both crops. In eggplant, 1 mg/L LMF treatment showed the maximum germination (91.6%), whereas, in finger millet, 0.1 and 0.5 mg/L LMF recorded a substantial increase in germination percentage (41.6 and 46%). Maximum fresh weight (FW) was noted with 1.0 mg/L LMF, and 1.0 mg/L LMF and 0.5 mg/L HMF showed maximum dry weight (DW) in eggplant. In finger millet, maximum DW was observed in 0.5 mg/L LMF and 1.0 mg/L HMF. Maximum biomass was noted in the 0.1 mg/L LMF treated group in the case of callus growth in eggplant. Similarly, the shoot tip initiation, proliferation, and plantlet regeneration were significantly improved with fucoidan LMF (0.1 mg/L). In conclusion, fucoidan extracted from T. decurrens exhibiting natural growth promoter property is reported for the first time in this study. These fucoidan fractions, LMF and HMF, can be utilized as cost-effective supplements in plant tissue culture media replacing the commercial PGRs for micropropagation.

Zero-G Lab: A multi-purpose facility for emulating space operations - Miguel Olivares-Mendez; Mohatashem Reyaz Makhdoomi; Barış Can Yalçın; Zhanna Bokal; Vivek Muralidharan; Miguel Ortiz Del Castillo; Vincent Gaudilliere; Leo Pauly; Olivia Borgue; Mohammadamin Alandihallaj; Jan Thoemel; Ernest Skrzypczyk; et al. (Journal of Space Safety Engineering, 2023)

Peanut shell-derived photothermal absorber for solar desalination - T. Arunkumar; Higgins M. Wilson; Hyeong Woo Lim; Ali Zain Hameed; Sang Joon Lee (Desalination, 2023)

Waste are in the limelight: cost-effective waste materials for sustainable solar desalination - Thirugnanasambantham Arunkumar; Higgins M. Wilson; Sang Joon Lee (Clean Technologies and Environmental Policy, 2023)

A rationally designed hetero-assembly of 2D/2D Nitrogen-doped MXene/Graphene via supercritical fluid processing for high energy durable supercapacitors - K. Nasrin; M. Arunkumar; N. Koushik Kumar; V. Sudharshan; S. Rajasekar; D. Mukhilan; M. Arshad; M. Sathish (Chemical Engineering Journal, 2023)

Optimization of bamboo-based photothermal interfacial solar evaporator for enhancing water purification - Thirugnanasambantham Arunkumar; Hyeong Woo Lim; Higgins M. Wilson; Younghoon Suh; Sang Joon Lee (Environmental Science and Pollution Research, 2023)

The impacts of Mn ion incorporation on the structural, optical, and magnetic properties of hematite NPs - S. James Jayaseelan; K. Parasuraman; D. Benny Anburaj; M. Jothibas; B. Arunkumar (Nanotechnology for Environmental Engineering, 2023)

Direct, indirect, post-infection damages induced by coronavirus in the human body: an overview - Sivan Padma Priya; P. M. Sunil; Sudhir Varma; Carel Brigi; Mohammad Faruq Abd Rachman Isnadi; J. A. Jayalal; R. Arunkumar Shadamarshan; S. Suresh Kumar; Neela Vasantha Kumari; Rishi P. R. Kumar (VirusDisease, 2022)

Indian rosewood (Dalbergia latifolia Roxb.): biology, utilisation, and conservation practices - A. N. Arunkumar; Rekha Ravindranath Warrier; Mafatlal M. Kher; Jaime A. Teixeira da Silva (Trees, 2022)

Morphological and biochemical resistance traits of tomato cultivars against thrips and bud necrosis virus disease - B Jamuna; M Bheemanna; Hn Timmanna; Arunkumar Hosmani; Kandapal Kavita (International Journal of Tropical Insect Science, 2021)

Influence of meteorology, mobility, air mass transport and biomass burning on PM2.5 of three north Indian cities: phase-wise analysis of the COVID-19 lockdown - M. Arunkumar; S. Dhanakumar (Environmental Monitoring and Assessment, 2021)

Development of Improved Strategies for the Survival of Lactobacillus Plantarum MTCC 1407 in Probioticated Custard Apple Juice - M. Arunkumar; S. K. Divya; N. Mahesh; S. Balakumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

Genotyping of human adenoviruses circulating in Southwest India - C. Akhil; P. G. Suresha; S. Sabeena; M. Hindol; G. Arunkumar (VirusDisease, 2016)

Implications of Volume Exclusion: A Look at Thermodynamic Perspective of DNA-Hemoglobin Complexes and Their Reconstitutes Under Macromolecular Crowding - Priyanka D. Pal; Prabhakar M. Dongre; Arunkumar V. Chitre (Journal of Fluorescence, 2016)

“Is Macromolecular Crowding Overlooked?”- Effects of Volume Exclusion on DNA-Amino Acids Complexes and Their Reconstitutes - Priyanka D. Pal; Prabhakar M. Dongre; Arunkumar V. Chitre (Journal of Fluorescence, 2014)

Release modulation of highly water soluble drug using solid dispersion: impact of dispersion and its compressed unit - Punit B. Parejiya; Bhavesh S. Barot; Hetal K. Patel; Dharmik M. Mehta; Pragna K. Shelat; Arunkumar Shukla (Journal of Pharmaceutical Investigation, 2014)

Quercetin downregulates matrix metalloproteinases 2 and 9 proteins expression in prostate cancer cells (PC-3) - M. R. Vijayababu; A. Arunkumar; P. Kanagaraj; P. Venkataraman; G. Krishnamoorthy; J. Arunakaran (Molecular and Cellular Biochemistry, 2006)